2014
DOI: 10.1007/978-3-319-04220-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control and Prevention Considerations

Abstract: Due to the nature of their underlying illness and treatment regimens, cancer patients are at increased risk of infection. Though the advent and widespread use of anti-infective agents has allowed for the application of ever-greater immune-suppressing therapies with successful treatment of infectious complications, prevention of infection remains the primary goal. The evolutionary changes of microorganisms, whereby resistance to anti-infective therapy is increasingly common, have facilitated a paradigm shift in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…[10] Daniels and Talbot stated that the health care workers' hands provide a potential source for transmission of infectious agents so the effective decontamination of the hands decreases the risk of transmission of these agents to other patients. [11] Moreover, Toney-Butler et al reported that contaminated hands of health care workers are a main source of pathogenic spread. Therefore, proper hand hygiene reduces the microorganisms' proliferation, consequently reducing infection risk, length of stays, and overall healthcare cost.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Daniels and Talbot stated that the health care workers' hands provide a potential source for transmission of infectious agents so the effective decontamination of the hands decreases the risk of transmission of these agents to other patients. [11] Moreover, Toney-Butler et al reported that contaminated hands of health care workers are a main source of pathogenic spread. Therefore, proper hand hygiene reduces the microorganisms' proliferation, consequently reducing infection risk, length of stays, and overall healthcare cost.…”
Section: Discussionmentioning
confidence: 99%